2023
DOI: 10.3389/fmicb.2022.1028086
|View full text |Cite
|
Sign up to set email alerts
|

Nanotechnology in combating biofilm: A smart and promising therapeutic strategy

Abstract: Since the birth of civilization, people have recognized that infectious microbes cause serious and often fatal diseases in humans. One of the most dangerous characteristics of microorganisms is their propensity to form biofilms. It is linked to the development of long-lasting infections and more severe illness. An obstacle to eliminating such intricate structures is their resistance to the drugs now utilized in clinical practice (biofilms). Finding new compounds with anti-biofilm effect is, thus, essential. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 285 publications
0
27
0
1
Order By: Relevance
“…The current study supports the literature data that suggests metal-substituted cobalt ferrite nanoparticles have potential antibiofilm activity. Hence, the current finding recommends the potential possibilities of using Co 1 Ag x Fe 2– x O 4 ferrites in antibiofilm eradication …”
Section: Resultsmentioning
confidence: 99%
“…The current study supports the literature data that suggests metal-substituted cobalt ferrite nanoparticles have potential antibiofilm activity. Hence, the current finding recommends the potential possibilities of using Co 1 Ag x Fe 2– x O 4 ferrites in antibiofilm eradication …”
Section: Resultsmentioning
confidence: 99%
“…Thus, a wide variety of NPs with diverse characteristics and specificities are available and several reviews covering this topic can be found. Liu et al, Lv et al, Al‐Wrafy et al, and Mohanta et al have provided outstanding comprehensive reviews of existing NP‐based biofilm treatment, including all the information regarding material characteristics and the approach to eradicate biofilms, as well as the NPs classification and the challenges implied (Al‐Wrafy et al, 2022; Liu et al, 2019; Lv et al, 2023; Mohanta et al, 2023). Other focused reviews about organic, polymer‐based, and metal NPs against biofilms were made by Li et al, Birk et al, and Asare et al, respectively (Asare et al, 2022; Birk et al, 2021; Li et al, 2021).…”
Section: Nanomedicines For Biofilm Treatment: Challenges and Limitationsmentioning
confidence: 99%
“…Despite some promising in vitro results of many antimicrobial NPs and other types of nanomedicines, there have been few clinical trials conducted in comparison (Aflakian et al, 2023; Al‐Wrafy et al, 2022; Birk et al, 2021; Mohanta et al, 2023; Shreffler et al, 2019). Apart from the lack of suitable in vivo models, the absence of precise regulatory frameworks tailored to nanomedicines complicates their clinical use approval.…”
Section: Nanomedicines For Biofilm Treatment: Challenges and Limitationsmentioning
confidence: 99%
“…Gần đây, g-C3N4 đã thu hút nhiều sự chú ý về ứng dụng xúc tác quang tách nước tinh khiết và phân hủy chất hữu cơ gây ô nhiễm dưới ánh sáng khả kiến [2]. Vật liệu này có nhiều lợi thế như có vùng cấm khoảng 2,7 eV, khả năng sản xuất với quy mô lớn, giá thành hợp lý, phương pháp tổng hợp đơn giản, độ bền hoá cao và thân thiện với môi trường nên được sử dụng phổ biến và rộng rãi [3]. g-C3N4 được sử dụng để phân hủy các chất ô nhiễm hữu cơ, tách nước, khử CO2.…”
Section: Giới Thiệu Chungunclassified